Ett slott i romantikens lövsal - Håkansson, Carin; Pihel, Johan (2011)

(untitled)
The work presented here aims to give the owners of Château du Grand Val, Roland and Marie Nilsson d’Aubigné an integrated creative forest management plan in which their goals with the property is heeded, and where the plan is so clear that they can follow it without much difficulty. This work has come about through the normal processes of forest management plans, landscape architectural proposals as well as through field trips, field and literature studies, and our combined experience from our studies. The study visits, both on location in Brittany, France, but also in other places, as for instance Högestad, has provided the background information that formed the basis of our analysis and the proposal that is derived thereof. Some suggestions, which we consider important to the overall impression of the property, is provided a more focused and detailed solution, while other parts, which are important but can either benefit from having dynamics in the design process or will be adapted to adjacent sites, are developed using a more general approach. In some cases several possible development principles are presented. The proposal presents a detailed plan for the management of the forest from the experience, wildlife and forestry economic standpoint. The results are presented in both text and illustrations. Emphasis was put to promote balance between the three aspects of the forest so that all three reach optimal conditions.